Signal transduction pathways in Synechocystis sp. PCC 6803 and biotechnological implications under abiotic stress. (June 2015) - Liu, Z.X.; Li, H.C.; Wei, Y.P.; Chu, W.Y.; Chong, Y.L.; Long, X.H.; Liu, Z.P.; Qin, S.; Shao, H.B.
Abstract Cyanobacteria have developed various response mechanisms in long evolution to sense and adapt to external or internal changes under abiotic stresses. The signal transduction system of a model cyanobacterium Synechocystis sp. PCC 6803 includes mainly two-component signal transduction systems of eukaryotic-type serine/threonine kinases (STKs), on which most have been investigated at present. These two-component systems play a major role in regulating cell activities in cyanobacteria. More and more co-regulation and crosstalk regulations among signal transduction systems had been discovered due to increasing experimental data, and they are of great importance in corresponding to abiotic stresses. However, mechanisms of their functions remain unknown. Nevertheless, the two signal transduction systems function as an integral network for adaption in different abiotic stresses. This review summarizes available knowledge on the signal transduction network in Synechocystis sp. PCC 6803 and biotechnological implications under various stresses, with focuses on the co-regulation and crosstalk regulations among various stress-responding signal transduction systems.